1998
DOI: 10.1002/(sici)1521-4141(199810)28:10<3057::aid-immu3057>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

IL-7 promotes the survival and maturation but not differentiation of human post-thymic CD4+ T cells

Abstract: This study examines the influence of IL-7 on post-thymic CD4+ T cells using cord blood as a model system. Survival of naive cord blood T cells in the presence of IL-7 alone was significantly prolonged by up-regulating bcl-2, thereby preventing apoptosis while maintaining maximal cell viability. Cultures without IL-7 showed high rates of apoptosis resulting in 50% cell death by day 5 of culture. Upon phorbol 12-myristate 13-acetate + ionomycin stimulation, accumulation of cytoplasmic IL-2 was similar to that ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
60
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 24 publications
4
60
1
Order By: Relevance
“…These cytokines, which include IL-2, IL-4, and IL-7, play a vital role in the development, expansion, and survival of the lymphoid system (11). Previous work by our group and others has shown that IL-7 can induce expansion and survival of these cells while maintaining a naive phenotype (6,10,12). The antiapoptotic effect of IL-7 has been shown to be in part due to its up-regulation of the antiapoptotic protein Bcl-2 (13,14).…”
supporting
confidence: 91%
“…These cytokines, which include IL-2, IL-4, and IL-7, play a vital role in the development, expansion, and survival of the lymphoid system (11). Previous work by our group and others has shown that IL-7 can induce expansion and survival of these cells while maintaining a naive phenotype (6,10,12). The antiapoptotic effect of IL-7 has been shown to be in part due to its up-regulation of the antiapoptotic protein Bcl-2 (13,14).…”
supporting
confidence: 91%
“…The BLV-binding receptor was also induced on umbilical cord T lymphocytes following their culture in the presence of the IL-7 cytokine (Fig. 4A), a T cell survival factor that can stimulate proliferation of these T cells without inducing an extensive activation profile (42,43). These data are very reminiscent of the expression profile of the HTLV receptor Glut1 (29,44) and indicate that the BLV Env-binding receptor is a novel cell cycle entry/proliferation marker in both B and T lymphocytes.…”
Section: The Blv-binding Receptor Is Up-regulated At Early Time Pointsupporting
confidence: 65%
“…For example, peripheral T cells from IL-7R␣ Ϫ/Ϫ mice show impaired proliferation and increased apoptosis after TCR engagement. Therefore, IL-7R␣ expression appears to be important in the maintenance and strength of the immune response (34,45,46). In this regard it is noteworthy that TCR stimulation decreases IL-7R␣ expression.…”
Section: Discussionmentioning
confidence: 99%